Increased expression of interferon-stimulated gene 15 (ISG15) in cervical cells on day 14 of pregnancy in Holstein heifers - Graciana R. Mendina; Victoria de Brun; Maria de Lourdes Adrien; Victoria Pons; Rodrigo Vivian Paradizo; Jorge Gil; Cecilia C. Rocha; Mario Binelli; Ana Meikle (JDS Communications)
In cattle, expression of IFN-stimulated genes in the female reproductive tract has been reported as an early pregnancy diagnostic tool, as early as d 17 of pregnancy. The hypothesis of this study was that expression of ISG15 in the cervix of pregnant heifers is increased on d 14 of pregnancy. The objective was to compare the expression of ISG15 in cervical cells between pregnant and cyclic heifers (control, sham-inseminated) on d 14, 16, and 18 after insemination (d 0). Holstein heifers were submitted to an estrus synchronization protocol and inseminated with extender only (“control,” n = 6), or with regular semen (n = 15). Heifers were classified as pregnant (n = 10) by ultrasound at d 30 through the detection of a viable embryo with a heartbeat. Blood samples from the coccygeal vein were collected to determine serum progesterone concentrations on d 14, 16, and 18. The expression of ISG15 and PGR in cervical cells collected through cytobrush was measured on d 14, 16, and 18. A receiver operating characteristic (ROC) curve was calculated to quantify the pregnancy diagnostic accuracy of ISG15 and PGR expression. The expression levels of ISG15 in cervical cells were significantly greater in pregnant compared with control heifers on d 14, and remained greater on d 16 and 18, whereas differences in PGR were observed only on d 18. Scatter plots and ROC analyses showed the most accurate prediction of pregnancy for ISG15 on d 16. In conclusion, cervical cells express greater ISG15 mRNA in pregnant versus control heifers as early as d 14 postinsemination, with the best accuracy on d 16.